The genus Mitreola (Loganiaceae) in Mexico - Islas-Hernández, Carla Sofia; Ochoterena Booth, Helga; Valencia-Ávalos, Susana; Alvarado-Cárdenas, Leonardo Osvaldo (Instituto de Ecología, A.C., 2018)
Background and Aims: Loganiaceae is a group of tropical plants, which have been poorly studied in Mexico. Some of the taxa are little known in terms of their taxonomy and distribution, such as the genus Mitreola, where additionally some of the species have nomenclatural problems. This work focuses on a taxonomic review of Mitreola petiolata and solves the nomenclatural problems that the species has had over the years.Methods: A review of specimens in different herbaria was carried out, specialized literature to obtain descriptions and taxonomic keys, the number of species of the genus and their distribution, as well as the circumscription and nomenclatural problems of the taxon. To obtain the palynological data, material from mature flowers was acetylated and revised with the scanning electron microscope. From these data an evaluation of the conservation situation was obtained.Key results: Mitreola petiolata has a pantropical distribution and is the only species of the genus present in the country, growing from Tamaulipas and Sinaloa to the Yucatán Peninsula. In spite of the morphological variation of structures such as the leaves or the lobes of the capsule, the characters of taxonomic importance (dichotomic inflorescence, subsessile flowers and stamens inserted close to the base of the corolla) remain constant.A review for M. petiolata, a dichotomous key, data on its distribution and conservation status in the country is provided. Detailed information on the micromorphology of pollen grains is presented, the first made for the species. The category of Least Concern is suggested, due to its wide distribution.Conclusions: The constant revision and curation of biological collections, keeps knowledge of taxa updated. This is the case of Mitreola petiolata, for which an update of its systematics, distribution and state of conservation is provided.